2014
DOI: 10.1021/am5006282
|View full text |Cite
|
Sign up to set email alerts
|

SERS Detection and Removal of Mercury(II)/Silver(I) using Oligonucleotide-Functionalized Core/Shell Magnetic Silica Sphere@Au Nanoparticles

Abstract: Heavy metal ions, such as Hg(2+) and Ag(+), pose severe risks in human health and the environment. For sensitive detection and selective removal of Hg(2+) and Ag(+) ions, here, we demonstrate a surface-enhanced Raman scattering (SERS)-active platform by employing the oligonucleotide-functionalized magnetic silica sphere (MSS)@Au nanoparticles (NPs). This system exploits mismatched T-Hg-T and C-Ag-C bridges to capture Hg(2+) and Ag(+) ions, exhibiting excellent responses for Hg(2+) ions in the range of 0.1-1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(63 citation statements)
references
References 47 publications
0
62
0
1
Order By: Relevance
“…Since the discovery of (SERS) in 1974 (Fleischmann et al 1974), it has aroused intense interest due to its high sensitivity and specificity in the detection of analytes (Su et al 2012;Liu et al 2014;Han et al 2015). The enormous SERS enhancement effect has enabled this technology to be widely applied in biology, medicine pharmacy, environmental monitoring, national security and other fields over the decades (Ye et al 2012;Zong et al 2012;Yang et al 2014;Wang et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of (SERS) in 1974 (Fleischmann et al 1974), it has aroused intense interest due to its high sensitivity and specificity in the detection of analytes (Su et al 2012;Liu et al 2014;Han et al 2015). The enormous SERS enhancement effect has enabled this technology to be widely applied in biology, medicine pharmacy, environmental monitoring, national security and other fields over the decades (Ye et al 2012;Zong et al 2012;Yang et al 2014;Wang et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic substrates could efficiently adsorb the analyte molecules from environmental matrix and can be easily separated and removed from the matrix by a magnet, providing a convenient platform for the sensitive detection and selective removal of Hg 2+ . For example, Liu et al (2014) proposed a SERS-active platform with the oligonucleotide-functionalized magnetic silica sphere (MSS)@ Au NPs (Fig. 8D).…”
Section: Sandwich Structural-based Methodsmentioning
confidence: 99%
“…[153][154][155][156][157][158][159][160][161][162][163][164][165] Through monitoring the different emission of quantum dots, Freeman et al reported a uorescent sensor for multiplex detection of Hg 2+ and Ag + using nucleic acid-functionalized quantum dots. 161 The detection limit can reach 10 nM for Hg 2+ and 1 mM for Ag + .…”
Section: Simultaneous Detection Of Heavy Metal Ions (Pb 2+ Hg 2+ Anmentioning
confidence: 99%
“…12). 165 In this sensor, MSS@AuNPs are functionalized by two types of ssDNA with different capture segments and two different Raman reporter-labeled ssDNAs, respectively. In the presence of Hg 2+ and Ag + , the T-T mismatch can effectively capture Hg 2+ to form the T-Hg 2+ -T bridges, and the C-C mismatch can effectively capture Ag + to form the C-Ag + -C bridges, enabling the generation of plasmonic hotspots and consequently the enhanced SERS signals.…”
Section: Simultaneous Detection Of Heavy Metal Ions (Pb 2+ Hg 2+ Anmentioning
confidence: 99%